2018
DOI: 10.1590/1807-57622017.0679
|View full text |Cite
|
Sign up to set email alerts
|

Formação interprofissional e produção do cuidado: análise de uma experiência

Abstract: Resumo Este artigo tem como objetivo apresentar e analisar uma experiência de formação interprofissional que ocorre desde 2008, envolvendo estudantes do terceiro ano de graduação dos cursos de Educação Física, Nutrição, Psicologia, Fisioterapia e Terapia Ocupacional de uma universidade pública. Ao longo do semestre, equipes mistas de estudantes, supervisionadas por duplas de docentes, também de diferentes áreas profissionais, realizam atendimentos semanais e elaboram projetos de cuidado para pessoas/grupos sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 9 publications
1
3
0
20
Order By: Relevance
“…In the students' reports, the perception of their own professional role and that of the others was present, corroborating the proposal of IPE (14)(15) and the studies that have shown the development of this competency in the interrelationships between professionals from different areas (12)(13)(14)(15)(16)(17)(18)(19)(29)(30)(31)(32)(33)(34)(36)(37)(38) . (18)(19)(36)(37)(38) . trust and unity within the team (39)(40)(41)(42) .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the students' reports, the perception of their own professional role and that of the others was present, corroborating the proposal of IPE (14)(15) and the studies that have shown the development of this competency in the interrelationships between professionals from different areas (12)(13)(14)(15)(16)(17)(18)(19)(29)(30)(31)(32)(33)(34)(36)(37)(38) . (18)(19)(36)(37)(38) . trust and unity within the team (39)(40)(41)(42) .…”
Section: Discussionsupporting
confidence: 76%
“…The recognition of the roles and responsibilities involved in collaborative practice was evidenced in several reports of the students of this research. The development of respect for the other professionals in training through the experience of learning together favors the elimination of stereotypes (16,(32)(33)(34)(36)(37)(38) . In the students' reports, the perception of their own professional role and that of the others was present, corroborating the proposal of IPE (14)(15) and the studies that have shown the development of this competency in the interrelationships between professionals from different areas (12)(13)(14)(15)(16)(17)(18)(19)(29)(30)(31)(32)(33)(34)(36)(37)(38) .…”
Section: Discussionmentioning
confidence: 99%
“…Neste sentido, algumas universidades já caminham para superar tal fragilidade. Os trabalhos de Batista (2012), Candido, Rossit e Oliveira (2018), Capozzolo et al (2018), Ferreira et al (2013), apresentam propostas nas quais a interprofissionalidade é um dos elementos estruturantes da formação em educação física.…”
Section: Introductionunclassified
“…A interprofissionalidade, contemplada na presente edição do PET-Saúde, vem consolidar o trabalho colaborativo como eixo transversal articulador do ensino e da produção de saúde pelos diversos atores que atuam na atenção primária, em prol do usuário, com vistas a tornar a assistência mais resolutiva e de maior qualidade, minimizando omissões e duplicações no cuidado (Vendruscolo et al, 2020;Capozzolo et al, 2018). Segundo Dias et al (2016), ela se faz por meio da comunicação efetiva e articulada entre os diferentes profissionais envolvidos na assistência.…”
Section: Introductionunclassified